Puerperal and Intrapartum Group A Streptococcal Infection - Eyal Y. Anteby; Simcha Yagel; Josef Hanoch; Mervyn Shapiro; Allon E. Moses (Hindawi Limited, 1999)
Objective: To determine the demographic and clinical variables characteristic of non-epidemic intrapartum or puerperal group A streptococcal (GAS) infection.